Improving Ability to Write Complex Procedure Text Using Process Approach for Students of SMK Negeri 2 Bungoro - Hanana Maulida; Muhammad Dahlan (Universitas Muhammadiyah Enrekang, 2022)
The purpose of this study was to describe the implementation of learning to write complex procedural texts using a process approach for students of SMK Negeri 2 Bungoro and to describe the improvement in learning to write complex procedure texts using a process approach for students of SMK Negeri 2 Bungoro. The process approach is a learning method that is still not used in the process of learning to write complex procedure texts. The purpose of this research is to describe how learning to write complex procedure texts is increased by using a process approach. This type of research is class action research which consists of two cycles, each cycle being held in two meetings. Research procedures include planning, implementation, action, observation, and reflection. The subjects in this study were 32 students of SMK Negeri 2 Bongoro. The method in this study used a qualitative research method in the form of PTK with observation, interview and documentation methods. The results showed that in the first cycle that was completed individually, namely 14 people (34.75%) out of 32 students who met the KKM completeness criteria, the average classical learning outcome was 63.19. Whereas in the second cycle there was an increase of 28 people (87.5%) out of 32 students fulfilling the KKM classical average learning outcomes of 80.56. Based on the results of this study, learning to write complex procedure texts using a process approach for students of class XI TKR 1 SMK Negeri 2 Bungoro has increased. Keyword: Writing, Complex Procedure Text, Process Approach